La mujer directiva en España : Catalizadores e inhibidores en las decisiones de trayectoria profesional - Anca, Celia de; Aragón, Salvador (IE University, 2007)
The last few years have seen important changes in the Spanish business environment with regard to women executives and their integration in business organisations. Nevertheless, figures still show a large quantitative difference on boards of directors and in the top levels of company management. Both public and private sectors have launched a series of initiatives designed to eliminate this imbalance. After carrying out studies in recent years, however, we believe that these initiatives are nearly all centred on the external barriers that hinder women’s promotion. Meanwhile there are major hurdles at an internal level that make women’s advancement difficult, and which only a change in culture and perspective can resolve it. We believe that training focused on individual perceptions of women in its career management can play a fundamental role in meeting the goal of total integration of women in the labour market
Keywords: Diversity;Women;Gender;Work-life balance;Gender options;Gender choices; Diversity; Women; Gender; Work-life balance; Gender options; Gender choices; ODS 9 - Industria, innovación e infraestructura